Journal Economics, business & accountancy : SUCCESSES AND FAILURES OF AICPA INITIATIVES: IMPACT OF DIVERSITY DECLINE ON MINORITIES - Foma, Elizabeth (PPPM Perbanas, 2013)
This is a qualitative research examining the impact of diversity in the Certified Public Accounting(CPA) profession and the successes and failures of the American Institute of Certified PublicAccountants (AICPA) initiatives to address this issue. It also examined current state of diversity inthe CPA profession and found that while the actual head count of minorities in the professionincreased, the percentage of representation dropped.